2011
DOI: 10.1007/s00270-011-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Arterial Embolization with Doxorubicin-Loaded Superabsorbent Polymer Microspheres in a Rabbit Liver Tumor Model

Abstract: Objectives To study the pharmacokinetic profile after hepatic arterial embolization with superabsorbent microspheres (QuadraSpheres) loaded with doxorubicin. Materials and Methods Rabbits with hepatic VX2 tumors were treated with intra-arterial administration of QuadraSpheres loaded with doxorubicin, or transarterial chemoembolization (TACE) using doxorubicin, Lipiodol and Embospheres, or hepatic arterial infusion (HAI) of doxorubicin. Tumor specimens were evaluated by fluorescence microscopy, and plasma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 36 publications
(38 reference statements)
5
27
0
Order By: Relevance
“…These new vehicles may offer the opportunity to implement a higher level of standardization to HCC treatment (1). Previous studies have shown that TACE with drug-eluting microspheres has an improved pharmacokinetic profile and results in effective tumor killing in both preclinical animal models and clinical studies in humans (4)(5)(6)(7)(8). The PRECISION V randomized trial did not reach its primary end point of improved objective response at 6 months, but did identify relative benefit of using drugeluting microspheres to achieve a higher response rate in high-risk patients and lower toxicity overall (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These new vehicles may offer the opportunity to implement a higher level of standardization to HCC treatment (1). Previous studies have shown that TACE with drug-eluting microspheres has an improved pharmacokinetic profile and results in effective tumor killing in both preclinical animal models and clinical studies in humans (4)(5)(6)(7)(8). The PRECISION V randomized trial did not reach its primary end point of improved objective response at 6 months, but did identify relative benefit of using drugeluting microspheres to achieve a higher response rate in high-risk patients and lower toxicity overall (8).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the advantages of higher response rates in high-risk patients, lower hepatic and with positively charged moieties in drugs such as doxorubicin by an ion-exchange mechanism and allow loading of the drug from dilute solutions. Use of drug-eluting microspheres for TACE leads to high and sustained intratumoral doxorubicin concentrations, as well as decreased systemic drug levels and toxicity (3)(4)(5)(6)(7)(8).…”
Section: Vascular and Interventional Radiologymentioning
confidence: 99%
“…Unlike the other microspheres HepaSphere is the only loadable microsphere that is more elastic and has a better contact with the vessel wall of the tumor causing necrosis [9,10,11,12]. HepaSphere loading and elution occurs in the same time window for the two smaller available sizes ranging from 15 min to 2 h and 1 h to 14 days, respectively [13]. Animal studies with HepaSphere have shown that bland HepaSphere presents lower cancer cell killing effect compared with HepaSphere loaded with doxorubicin [14].…”
mentioning
confidence: 98%
“…Although such interactions remain theoretical, they are possible as systemic concentrations of doxorubicin can be identified following TACE. For example, in one study using a rabbit liver tumor model, plasma concentration of doxorubicin after TACE was as high as 360.5 ng/mL [18] . In a phase 2 study designed to establish the efficacy and safety of drug eluting beads loaded with doxorubicin for the TACE treatment of HCC patients, doxorubicin Cmax and AUC were 78.97 ± 38.3 ng/mL and 662.6 ± 417.6 ng/mL respectively [19] .…”
Section: Discussionmentioning
confidence: 99%